The role of institutional innovation and artificial intelligence in the corporate eco-innovation - a case study of high-tech enterprises in Liaoning province of China - Lin, Xuanyu; Hu, Xiheng; Qu, Yi; Wei, Zhiruo (Journal of Asian Business Strategy, 2024)
This research investigates the intricate interplay of institutional factors and technological adoption in the context of corporate ecological innovation. Grounded in the New Institutionalism Theory and the Technology-Organization-Environment (TOE) framework, the study explores how formal and informal institutional innovations shape the behavior and capabilities of companies engaged in ecological innovation in Liaoning Province, China. Furthermore, the research examines the role of Artificial Intelligence (AI) in promoting ecological innovation. The study classifies AI into three categories: data analytics and predictive AI, automation and intelligent production AI, and customer service and user experience AI. These dimensions are investigated in terms of their influence on ecological innovation, revealing how each element contributes to enhancing companies’ capabilities in addressing ecological challenges. The research proposes hypotheses regarding the positive influence of these AI dimensions on ecological innovation outcomes. The findings from this research contribute to the education of the intricate dynamics between institutional innovations, technological adoption, and corporate ecological innovation. The insights garnered are crucial for policymakers, businesses, and researchers striving to cultivate sustainable practices and innovation in ’the contemporary economic and environmental milieu.